LINGUOCULTURAL AND AESTHETIC EXPRESSION OF NATIONAL MENTALITY IN LITERARY WORKS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article discusses the means of expressing national mentality, their linguoculturological significance, and the functions they perform in a literary work.